Prevalence and Sociodemographic Factors of Overweight and Obesity among Pakistani Adults - Muhammad Asif (Journal of Obesity & Metabolic Syndrome, 2020)
Background : : Obesity is a serious public health problem that is growing alarmingly worldwide. The main objective of this study is to examine the current prevalence of overweight and obesity among Pakistani adults and to identify the sociodemographic factors that are associated with overweight and obesity. Methods : : Secondary data from a population-based household survey (the Pakistan Panel Household Survey) were used for this study. A total of 10,063 participants (3,916 men and 6,147 women) were included. Overweight and obese individuals were identified using the World Health Organization-recommended cutoffs for body mass index (kg/m2). Along with descriptive statistics, the Pearson chi-square test was used to investigate the association among categorical variables. Odds ratios (ORs) along with 95% confidence intervals (CIs) were estimated using univariate logistic regression analysis to evaluate the most significantly associated risk factors for overweight/obesity. Results : : The mean age and body mass index of the participants were 38.2 years and 22.9 kg/m2, respectively. Overall, 22.8% of the participants (23.9% of the women and 21.1% of the men) were overweight, and 5.1% (6.3% of the women and 3.2% of the men) were obese. Sociodemographic factors, such as sex, marital status, and residential area, were significantly associated with body mass index categories. Women (OR, 1.34; 95% CI, 1.23–1.47; P<0.01), ever-married individuals (OR, 1.92; 95% CI, 1.70–2.16; P<0.01), and individuals living in urban areas (OR, 1.23; 95% CI, 1.12–1.35; P<0.01) were more likely to become overweight/obese than their counterparts. Conclusion : : We have found the excess weight problem to be quite high in the Pakistani adult population. The government and other health agencies should take initiatives in launching programs about nutritional awareness for adults to prevent obesity.